BUILDING AND DESIGNING THE DIGITAL DATABASE FRAME OF THE OCEANOGRAPHY AND MARINE ENVIRONMENT OF THE NINH THUAN - BINH THUAN COASTAL WATERS - Tien, Ngo Manh; Huan, Nguyen Huu; Chung, Tran Van; Son, Tong Phuoc Hoang; Thach, Vo Trong; Thuy, Pham Thi Thu (Vietnam Journal of Marine Science and Technology, 2018)
This paper presents the building and designing of the digital database frame about the oceanographic and environmental elements of the coastal waters of Ninh Thuan and Binh Thuan provinces, based on the integration of data from the observed, multi-temporal remote sensing as well as simulated sources. Especially, VNREDSat-1 the first remote sensing imagery of Vietnam with high resolution also got the attention in building the digital database frame. The building of the digital database frame is the first important step in order to achieve an overview of data’s structure, then to build the database’s structure. The database’s structure is built in the form of B-tree which optimize the operation when updating the data.